Does climate change drive up government healthcare costs in the European Union? - Socol, Adela; Iuga, Horia; Socol, Dragoș; Iuga, Iulia Cristina (Frontiers in Environmental Science, 2023)
The continuous growth in average temperature around the world, caused especially by CO2 emissions, generates climate changes significantly impacts not only economic or social domains, but also human health. The previous literature provides evidence of degradation of human health due to climate change and emphasizes pressure on governments to increase government spending on health. The aim of this study is to analyze the impact of climate change, expressed by temperature and CO2 emissions, on healthcare spending in the European Union member states using available data from 2000 to 2020. In addition to prior research, this paper incorporates supplementary control variables such as governance, macroeconomic factors (GDP and inflation) and human development index. To capture the dynamic impact of climate change on healthcare expenditure, we use the Generalized Method of Moments (GMM) technique and the panel VAR Granger causality method. Empirical findings suggest that an increase in temperature and CO2 emissions levels, along with improvements in governance, economic growth, inflation, and human development, contribute to higher healthcare expenditures. Rising temperature and CO2 emissions are directly increasing the health burden on individuals' health and force governments to enhance health spending. The paper is notable for its comprehensive approach, filling a significant gap in existing literature by combining climate change variables with governance, economic and human development indicators. The study provides policymakers with valuable insights into how climate change and other governance, economic and human factors impact healthcare spending. Global warming appears as a topic directly correlated with the governmental health spending burden and highlights the need for government involvement in mitigating global warming, reducing pollution and gas emissions.